Construction and Use of Transposon MycoTetOP2 for Isolation of Conditional Mycobacteria Mutants - Riggs-Shute, Sarah D.; Falkinham, Joseph O.; Yang, Zhaomin (Frontiers in Microbiology, 2020)
Mycobacteria are unique in many aspects of their biology. The development of genetic tools to identify genes critical for their growth by forward genetic analysis holds great promises to advance our understanding of their cellular, physiological and biochemical processes. Here we report the development of a novel transposon, MycoTetOP2, to aid the identification of such genes by direct transposon mutagenesis. This mariner-based transposon contains nested anhydrotetracycline (ATc)-inducible promoters to drive transcription outward from both of its ends. In addition, it includes the Escherichia coli R6K origin to facilitate the identification of insertion sites. MycoTetOP2 was placed in a shuttle plasmid with a temperature-sensitive DNA replication origin in mycobacteria. This allows propagation of mycobacteria harboring the plasmid at a permissive temperature. The resulting population of cells can then be subjected to a temperature shift to select for transposon mutants. This transposon and its delivery system, once constructed, were tested in the fast-growing model Mycobacterium smegmatis and 13 mutants with ATc-dependent growth were isolated. The identification of the insertion sites in these mutants led to nine unique genetic loci with genes critical for essential processes in both M. smegmatis and Mycobacterium tuberculosis. These results demonstrate that MycoTetOP2 and its delivery vector provide valuable tools for the studies of mycobacteria by forward genetics.